The impact of Mexico-United States cooperation in the fight against money laundering - Vargas Rojas, Keyla Harummi (2016)
This article describes the effect of the relationship between Financial Intelligence Units of Mexico and the United States to investigate unusual dollar inflows in Mexico and to detect a transnational network of money launderers in 2012, 2013 and 2014. This impact was measured taking into account the evolution of cooperation between the Units through their annual reports and official documents together with the annual report of the Egmont Group of Financial Intelligence Units. The process of exchange of information between the two institutions is analyzed and its relationship evaluated regarding the construction of the requires intelligence to articulate arrest warrants and money laundering. It is concluded that the impact has been beneficial for both countries, as there are successful cases of detention of criminals for money laundering through the joint work of the Units.